Decision Support Enhancement for Player Substitution in Football: A Design Science Approach - Kröckel, Pavlina (Business Information Systems Workshops, 2017)
Football players are constantly being tracked during the live games by means of automated tracking technologies. Every event that happens on the field is recorded in a who-what-where-when fashion. These data are used in pre- and post-match analyses to improve strategies and tactics. To date such data have not yet been used for in-game decision making. Considering the impact of the substitute players on the final outcome of the game, this paper proposes an approach for enhancing the substitution decision. The goal is to support the coach and his staff during live matches by developing an algorithm or using an existing analytic method which will evaluate and rate the players’ performance and recommend a player that should leave the gam
Keywords: Football; Soccer; Substitution; Decision support; Design science